Novel imaging classification system of nodal disease in human papillomavirus‐mediated oropharyngeal squamous cell carcinoma prognostic of patient outcomes. Issue 6 (26th February 2021) - Sabiq, Farahna; Huang, Kitty; Patel, Adarsh; Banerjee, Robyn; Debenham, Brock; Lau, Harold; Skarsgard, David; Chen, Guanmin; Lysack, John T.; Quon, Harvey C.
Abstract: Background: Matted nodes in human papillomavirus (HPV)‐mediated oropharyngeal squamous cell carcinoma (OPC) is an independent predictor of distant metastases and decreased overall survival. We aimed to classify imaging patterns of metastatic lymphadenopathy, analyze our classification system for reproducibility, and assess its prognostic value. Methods: The metastatic lymphadenopathy was classified based on radiological characteristics for 216 patients with HPV‐mediated OPC. Patient outcomes were compared and inter‐rater reliability was calculated. Results: The presence of ≥3 abutting lymph nodes with imaging features of surrounding extranodal extension (ENE), one subtype of matted nodes, was associated with worse 5‐year overall survival, overall recurrence‐free survival, regional recurrence‐free survival, and distant recurrence‐free survival ( p  ≤ 0.03). Other patterns were not significantly associated with outcome measures. Overall inter‐rater agreement was substantial ( κ = 0.73). Conclusion: One subtype of matted nodes defined by ≥3 abutting lymph nodes with imaging features of surrounding ENE is the radiological marker of worst prognosis.